A case of novel mutation of Cullin 3 gene in pseudohypoaldosteronism type II. Issue 6 (June 2022) - Wang, Liang; Nie, Muwen; Guo, Fan; Tian, Zhuang; Guo, Xiaoxiao; Zhang, Shuyang
Abstract : Pseudohypoaldosteronism type II (PHA II) is a rare inherited disease characterized by hypertension, hyperkalemia and metabolic acidosis. With the development of gene sequencing technology, more genetic mutations underlying PHA II were reported and the understanding of its pathogenesis has gone deep into the molecular level. Here, we present a juvenile case of PHA II. A novel missense mutation (c.1376 A>T) located in exon 9 of Cullin 3 ( CUL3 ) was found by whole-exome sequencing. The clinical manifestations were significantly improved after oral hydrochlorothiazide. This case enriches the genetic and clinical phenotype spectrum of PHA II and provides experience for diagnosing and treating the disease.